(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
When calculating systems on an elastic foundation, the generalized Reissner-Vlasov-Filomenko-Borodich model is traditionally used. Such models are acceptable for small displacements. For large displacements, there are some deviations from reality. The article discusses the calculation of the deformation of an underground pipeline laid on saline soil, corresponding to a nonlinear elastic foundation using a nonlinear model of the type [1], taking into account these shortcomings.